BUDGET IMPACT ANALYSIS IN THE USE OF RIBOMUSTIN® IN THERAPY OF THE FIRST LINE OF A MULTIPLE MYELOMA FOR PATIENTS MORE SENIOR 65 YEARS OLD - A. S. Kolbin; I. A. Vilyum; M. A. Proskurin; Yu. E. Balykina (Фармакоэкономика, 2015)
We have performed the first-ever Budget Impact Analysis (BIA) in a Russian context of bendamustine in the first line of therapy of a multiple myeloma for patients more senior 65 years old with clinical manifestations of a polineuropathy, which autological transplantation of stem cells isn’t shown. Research was conducted from a position of the state health system of the Russian Federation. Within the BIA the analysis of economic efficiency and availability of technology was carried also out to be allowing to estimate expediency of introduction of technology in the presence of the budgetary restrictions. It was as a result shown that use of bendamustine in comparing with strategy of a bortezomib is more preferable strategy from the point of view of BIA: application of a bendamustine allows to keep considerable budget funds – to 159 153 118 rub, thus the saved means allow to treat with this strategy in addition 29 patients during 25 month. It was defined that application of strategy of a bendamustin in comparison with the bortezomib involves smaller load of the budget, thus growth of efficiency is observed for indicator “time to disease progression”.